Cytotoxic effects of conjugated linoleic acids on human colon cancer cells (HT-29) - Achenef, Melaku Beyene; Abdul Kadir, Arifah; Othman, Fauziah; Goh, Yong Meng; Sazili, Awis Qurni (Veterinary Association Malaysia, 2009)
Conjugated linoleic acids (CLAs) are fatty acids found naturally in milk and meat products derived from ruminants and have been reported as anticarcinogenic agent in in vitro and in vivo studies. This study was conducted to assess the cytotoxic effects of cis-9, trans-II (c9,t 11), trans-1 0, cis-12 (t 1O,c12) and mixed isomers of CLA on human colon cancer cells (HT- 29). Cells were grown on RPMI 1640 media and treated with different concentrations of CLA isomers for 72 hours. The results were determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) cytotoxicity assay. The viability of HT-29 cells was reduced significantly (P < 0.05) by all CLA isomers tested in a dose dependent manner. The median inhibitory concentration (IS50) value varied with type of CLA isomer. Mixed and t10, c12 were significantly (P< 0.05) more potent than c9, t11 C12 isomer. It has been confirmed that c9, t11; t10, c12 and mixed isomers of CLA have cytotoxic effect on HT-29 cancer cells. Further studies are required to clarify their mechanism of action and to use them in the treatment and/or prevention of colorectal cancer.